Populations, biomass and food habits of ducks on the Fraser Delta intertidal area, British Columbia - Vermeer, Kees; Levings, Colin D (Wildfowl, 1977)
Hundreds of thousands of ducks, mostly Mallard Anas platyrhynchos Pintail A. acuta, American Wigeon A. americana, Green-winged Teal A. crecca carolinensis and Greater Scaup Aythya marila visit the Fraser Delta intertidal area from October through January. Surf Scoters Melanitta perspicillata are most numerous in August and early September. Scaup and scoters appear to prefer Boundary Bay over Sturgeon and Roberts Bank. The total duck biomass on the tidal flats has a peak of 9 kilograms per hectare in November, Mallard and American Wigeon accounting for more than half. Most dabbling ducks fed on marsh and other plants. Of six diving duck species investigated, Black M. nigra, Surf and White-winged Scoters M. fusca deglandi and Oldsquaws Clangula hyemalis fed primarily on bivalves, Common Goldeneyes Bucephala clangula on crustaceans and Greater Scaup on algae. The food habits differ with respect to feeding location as well as time of season. Oldsquaws used mostly subtidal waters, Surf Scoters between 0 and 3 fathoms below chart datum, White-winged Scoters the lower intertidal zone, Greater Scaup a muddy substrate closest to the shoreline and sheltered in Boundary Bay.